Keterampilan Mengajar Dosen secara Daring Terhadap Kepuasan Belajar Mahasiswa pada Mata Kuliah Pengantar Akuntansi - Euis Nessia Fitri (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2021)
Abstract: The teaching skills of lecturers are applied to the techniques of mastery and delivery of material so that certain innovations are needed which are adapted to online learning. Student learning satisfaction does not appear by itself, there needs to be a role for lecturers in giving a professional impression both in online teaching skills and mastery of the material. So that in the future, student satisfaction is expected to have a positive impact on student learning outcomes. This study aims to see whether or not the teaching skills of lecturers have an effect on student learning satisfaction. The sample in this study was 134 students, with data collection using a questionnaire. This research is a survey research using correlation analysis techniques and linear regression, where there is one exogenous variable and one endogenous variable. The exogenous variable is in the form of lecturer teaching skills, while the endogenous variable is learning satisfaction. The result of this research is that there is a positive effect of lecturer teaching skills on student learning satisfaction in introductory accounting courses. With a simple correlation value of 0.1194. So that the teaching skills of lecturers contributed to an increase in student learning satisfaction by 1.4%. This research is expected to be a reference for improvement for online learning system activities in order to increase student satisfaction value.